Metal detector / Mohammad Taufik Shahadan Soobri & Aminuddin Idham Halid - Soobri, Mohammad Taufik Shahadan; Idham Halid, Aminuddin (2015)
The purpose of performing Final Year Project 2 is to fulfil the course requirement of the Diploma Of Electrical Power Engineering at Uitm Kampus Pasir Gudang. The students need to nurture the experiences, knowledge and skills during finishing the project. It is as the first step before for the students to enter the real working environment. Metal detector is one of the project for final year project. Metal detector is an interesting device to detect metal nearby. It can be used as someone hobby or for the security screening. In security viewpoints, metal detector is an fundamental gear. At the same time, the metal detector, which is accessible in the business sector today, is expensive. Consequently this stands as an issue for specialists and for little applications. Consequently we have taken a try to draw out a metal detector of least cost.